Mitochondrial respiratory capacities are not linked to individual variation in hypoxia tolerance and standard metabolic rate in European seabass Dicentrarchus labrax - Elisa Thoral; Julie Nati; Jean‐Baptiste Quémeneur; Léann Lozac'h; Germain Salou; Alain Vergnet; Mathieu Besson; Marc Vandeputte; François Allal; Karine Salin; David J. McKenzie; Loïc Teulier (Journal of Fish Biology, 2026)
In hypoxic environments, fish attempt to regulate their metabolic rate as oxygen levels in the water decline. Individuals that have low energy requirements for maintenance – standard metabolic rate (SMR) – are expected to have higher hypoxia tolerance, measured as the critical water oxygen saturation threshold (S crit ) below which they cannot regulate SMR. These whole animal traits may, in turn, be linked to aspects of individual mitochondrial oxidative metabolism that underpin SMR. We therefore investigated, in European seabass Dicentrarchus labrax , whether inter‐individual variation in SMR and S crit , measured by whole animal respirometry, was correlated with elements of mitochondrial metabolism in liver and heart, measured by high resolution respirometry (HRR). Among the 96 fish studied, inter‐individual variation in S crit was dependent upon variation in SMR. However, there was no evidence for correlations between SMR or S crit and individual mitochondrial respiratory capacities. Our results indicate that individual variation in complex whole animal traits of respiratory metabolism cannot always be linked to variation in subcellular mitochondrial phenotypes.